STAKEHOLDER COLLABORATION IN STRENGTHENING THE DEVELOPMENT AGENDA SUSTAINABLE AREAS - Rasmini Rasmini; Arif Nugroho (Jurnal Scientia, 2023)
This research aims to elaborate on the role of collaboration between stakeholders in strengthening the sustainable regional development agenda. The era of decentralization means that regional development must be built by prioritizing collaborative principles from the village to sub-district level. Thus, collaboration is needed between stakeholders, especially the sub-district head, so that the development agenda can be realized. However, several obstacles are still encountered, such as the lack of competence and knowledge of sub-district heads in planning regional development agendas. This research uses an explanatory qualitative approach with in-depth interview methods and observations of the sub-district head in Sobong District, Pandeglang Regency. The research results found that the role of the sub-district head greatly contributes to strengthening collaboration between stakeholders in realizing the regional development agenda. This research also found that a collaboration strengthening scheme is needed so that the regional development agenda can be sustainable according to the national agenda.